The farm at Black Mountain College - Silver, David (Atelier Éditions, 2024)
From its founding in 1933 and over its 23 year history, Black Mountain College (BMC), the small liberal arts school in rural North Carolina, attracted artists, writers, and visionaries, including Anni and Josef Albers, Ruth Asawa, John Cage, Merce Cunningham, Willem de Kooning, Buckminster Fuller, Ray Johnson, Charles Olson, and M. C. Richards. Through original research, The Farm at Black Mountain College follows students, faculty, and farmers as they establish a campus farm in the 1930s, build a better farm in the 1940s, and watch it all collapse in the 1950s. We meet a new cast of BMC characters whose stories have seldom, if ever been explored, and whose adventures in agriculture shine a light on what exactly happened at BMC across the decades; from optimistic community building to its plunge into substance-addled scarcity. The farm was vital to BMC. Throughout the Depression and World War II it provided sustenance, while serving as a testing ground for self-sufficiency, communal living, and collaboration
Keywords: Black Mountain College; Geschichte 1933-1957; Bauernhof; Black Mountain College (Black Mountain, N.C.) / History; Black Mountain College (Black Mountain, N.C.) / Alumni and alumnae; Arts / Study and teaching (Higher) / North Carolina / Black Mountain; Arts / Experimental methods; Farms / North Carolina / Black Mountain; Agriculture / Study and teaching; Arts / Méthodes expérimentales; Exploitations agricoles / Caroline du Nord / Black Mountain; Agriculture / Étude et enseignement; Black Mountain College (Black Mountain, N.C.); Universities and colleges / Alumni and alumnae; Arts / Study and teaching (Higher); Farms; North Carolina / Black Mountain / https://id.oclc.org/worldcat/entity/E39PBJfmrqpgb94J3RMCCdyKh3; History